Iridoids of fenugreek (Trigonella-foenum-graecum L.) seed extract detected via LC-QTOF-MS analysis - Akbari, Sweeta; Nour, A. H.; Fayaz, Fahim; Noory, Valantena (Elsevier B.V., 2021)
Fenugreek seed is a traditional medicinal plant with a wide biological activity. In this study, iridoids (Asperulosidic acid (1), 7-O-Methylmorroniside (2), Gentiopicroside (3), Rehmannioside A (4), Loganic acid-6′-O-β-Dglucoside (5), Sweroside (6), Penstemoside (7), 6′-O-β-D-Glucosyl Gentiopicroside (8), Oleuropein (9)) in optimized microwave-assisted extract of fenugreek seed were detected for the first time. The identification of iridoid compounds was carried out by liquid chromatography quadrupole time-of-flight mass spectrometry coupled with electrospray ionization (LC-QTOF-MS-ESI) in positive ion modes and Fourier Transform Infrared Spectroscopy (FTIR) analysis. More than 400 compounds were detected via LC-QTOF-MS, while among them only 9 were iridoids. The presence of iridoid compounds was also confirmed with FTIR analysis. In positive ion mode, iridoids with formic acid as mobile phase associated in formation of three adducts [+ H, + Na + K]. However, in the case of negative ion no iridoid compound was observed in the extract.